2022
DOI: 10.3390/molecules27061846
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyridines Potentiate ATP-Induced Currents Mediated by the Full-Length Human P2X5 Receptor

Abstract: The P2X5 receptor, an ATP-gated cation channel, is believed to be involved in tumor development, inflammatory bone loss and inflammasome activation after bacterial infection. Therefore, it is a worthwhile pharmacological target to treat the corresponding diseases, especially in minority populations that have a gene variant coding for functional homotrimeric P2X5 channels. Here, we investigated the effects of dihydropyridines on the human full-length P2X5 receptor (hP2X5FL) heterologously expressed in Xenopus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…We are highly interested in human homotrimeric P2X1, P2X2, P2X3, P2X4, P2X7, and the heterotrimeric P2X2/3 receptors and the present SAR study focuses on these targets. The P2X5 and P2X6 receptors exist predominantly in the heterotrimeric form and are difficult to establish in a stable cell and are therefore excluded from the current SAR study. The prepared and commercially available nucleotides were screened in Ca 2+ flux assays at P2X1, P2X2, P2X2/3, P2X3, P2X4, and P2X7 receptors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are highly interested in human homotrimeric P2X1, P2X2, P2X3, P2X4, P2X7, and the heterotrimeric P2X2/3 receptors and the present SAR study focuses on these targets. The P2X5 and P2X6 receptors exist predominantly in the heterotrimeric form and are difficult to establish in a stable cell and are therefore excluded from the current SAR study. The prepared and commercially available nucleotides were screened in Ca 2+ flux assays at P2X1, P2X2, P2X2/3, P2X3, P2X4, and P2X7 receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, due to the rapid acyl transfer between the two vicinal alcohols, the regioisomeric mixtures of 2′-and 3′ esters were not separated and tested as mixtures. Four commercially available nucleotides with either differing stereochemistry at the 2′-O position (30) or introduction of substituents at the 2′-O position (27−29) were applied in the SAR evaluation as well (Table 4). The second set focused on commercially available ATP derivatives with modifications at the nucleobase at 2-, 8-, and N 6 -positions that enrich or reduce the electron density of the purine ring system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A stimulatory effect on inammatory processes may also be a side effect of nimodipine therapy (Scheme 6). 23 Using alkyne 1,4-DHPs 6a and substituted azides 6b for the synthesis of functionalized triazoles, Bijani et al (2022) described a copper-catalyzed azide-alkyne cyclization (CuAAC) reaction for the synthesis of a library of 1,4-DHP-based 1,2,3triazole derivatives 6 and assessed their cytotoxic potential on colorectal adenocarcinoma. The ndings suggested that the majority of these drugs exhibit substantial antiproliferative action, with IC 50 values ranging from 0.63 AE 0.05 to 5.68 AE 0.14 mM.…”
Section: A Decade Of Advancements In 14-dhp Synthetic Protocolsmentioning
confidence: 99%
“…Soon afterwards, the human exon 10 sequence was confirmed by a second research group when probing human genomic DNA with the exon 10 cDNA sequence for rP2X5 [14]. A full-length construct of human P2X5 was prepared for expression studies and the resultant full-length protein (444 aa subunit) assembled into a functional hP2X5 receptor [14, and then see [15][16][17][18]. However, the primary sequence of the full-length human P2X5 protein (hP2X5-fl) has never been listed in popular databases (such as Ensembl and Uni-portKB).…”
Section: Human P2x5 Receptors Hp2x5 Receptor Structurementioning
confidence: 99%
“…Of these cohorts, black Americans (7 of 10 subjects) express the full-length P2X5 protein whereas the other cohorts (white American, 46 of 46; middle Eastern ethnicity, 10 of 10; Chinese ethnicity, 10 of 10 subjects) express the truncated P2X5 protein (hP2X5A, hP2X5Δ 328−349 ). It has been argued that a single-nucleotide polymorphism (SNP) can occur at the 3′-splice site of exon 10 of the human P2X5 gene, replacing a critical thymidine (T) with a guanine (G) nucleobase [13][14][15][16]18]. The G-allele results in splice-skipping of exon 10, leading to truncated P2X5 subunits in those human cDNA samples tested so far (69 of 76 subjects; 91%) [15,16].…”
Section: Human P2x5 Receptors Hp2x5 Receptor Structurementioning
confidence: 99%